CCNA data center DCICN 640-911 : official cert guide - Odom, Wendell; Hintz, Chad. (Indianapolis, IN : Pearson Education, 2015)
Enables succeess on the exam the first time and is the only self-study resource approved by Cisco. Expert instructors and engineers Wendell Odom and Chad Hintz share preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills.
Includes a companion CD-ROM with practice questions for the exam, memory table exercises and answer keys, and a study planner tool.
Includes index.
oif 23/06/15
Loan
Keywords: Computer networks; CCNA data; DCICN